Hubungan Antara Fasilitas Belajar di Rumah Dengan Prestasi Belajar Selama Pembelajaran Daring pada Siswa Kelas IV SD se-Gugus 5 Kecamatan Lawang - Nina Ismatun Nadhiyah; Siti Mas’ula; Suhartono Suhartono; Nina Ismatun Nadhiyah; Siti Mas’ula (Universitas Negeri Malang, 2021)
Abstract: Learning facilities at home are all tools at home that are used to facilitate learning activities so that students can obtain learning achievements as expected. Learning achievement is the result achieved by students related to knowledge after participating in learning activities in the form of lesson values expressed in the form of numbers, letters, symbols, or numbers. This research aims to (1) describe learning facilities at home during online learning for fourth grade elementary school students, (2) describe learning achievement during online learning for fourth grade elementary school students, (3) find out a positive and significant relationship between home learning facilities with learning achievement during online learning in fourth grade elementary school students in cluster 5 Lawang District. This research is quantitative research which is included in the type of correlation. The results of data analysis obtained: (1) learning facilities at home during online learning for fourth grade elementary school students in cluster 5 Lawang District are included in the good category with an average of 12.9474 and a percentage of 72 percent is obtained, (2) learning achievement during learning online learning in fourth grade elementary school students in cluster 5 Lawang District is in the good category with an average of 79.4737 and a percentage of 79 percent is obtained, (3) there is a positive and significant relationship between learning facilities at home and learning achievement during online learning in fourth grade elementary school students in cluster 5 Lawang District with the acquisition of Sig. (2-tailed) less than 0.05 i.e. 0.000 less than 0.05, the value of rcount (Pearson Correlation) greater than r table is 0.711 greater than 0.181, and an asterisk (**) on the results of SPSS analysis which means that there is a relationship between variable X and variable Y. The value of r count is positive, which means that the direction of the relationship between variable X and variable Y is positive. The r count value of 0.711 is at the level of a strong relationship, which means that there is a significant relationship between the X variable and the Y variable. Abstrak: Fasilitas belajar di rumah adalah segala alat yang ada di rumah yang digunakan untuk memudahkan dan melancarkan kegiatan pembelajaran sehingga siswa dapat memperoleh prestasi belajar sesuai dengan yang diharapkan. Prestasi belajar merupakan hasil yang dicapai oleh siswa berkaitan dengan aspek pengetahuan setelah mengikuti kegiatan pembelajaran berupa nilai pelajaran yang dinyatakan dalam bentuk angka, huruf, simbol, ataupun angka. Penelitian ini bertujuan untuk (1) mendeskripsikan fasilitas belajar di rumah selama pembelajaran daring pada siswa kelas IV SD, (2) mendeskripsikan prestasi belajar selama pembelajaran daring pada siswa kelas IV SD, (3) mengetahui hubungan yang positif dan signifikan antara fasilitas belajar di rumah dengan prestasi belajar selama pembelajaran daring pada siswa kelas IV SD se-gugus 5 Kecamatan Lawang. Penelitian ini merupakan penelitian kuantitatif yang termasuk dalam jenis korelasional. Hasil analisis data diperoleh: (1) fasilitas belajar di rumah selama pembelajaran daring pada siswa kelas IV SD se-gugus 5 Kecamatan Lawang termasuk dalam kategori baik dengan rata-rata 12,9474 dan diperoleh persentase 72 persen, (2) prestasi belajar selama pembelajaran daring pada siswa kelas IV SD se-gugus 5 Kecamatan Lawang termasuk dalam kategori baik dengan rata-rata 79,4737 dan diperoleh persentase 79 persen, (3) terdapat hubungan yang positif dan signifikan antara fasilitas belajar di rumah dengan prestasi belajar selama pembelajaran daring pada siswa kelas IV SD se-gugus 5 Kecamatan Lawang dengan perolehan nilai Sig. (2-tailed) kurang dari 0,05 yaitu 0,000 kurang dari 0,05, nilai r hitung (Pearson Correlation) lebih dari r tabel yaitu 0,711 lebih dari 0,181, dan tanda bintang (**) pada hasil analisis SPSS yang berarti terdapat hubungan antara variabel X dengan variabel Y. Nilai r hitung bernilai positif yang berarti arah hubungan antara variabel X dengan variabel Y yaitu positif. Nilai r hitung yaitu 0,711 berada pada tingkat hubungan kuat yang berarti terdapat hubungan yang signifikan antara variabel X dengan variabel Y.